PERAN ORANG TUA DALAM PENDIDIKAN FORMAL ANAK PADA KELUARGA PETANI DI KECAMATAN SANGGAU LEDO - Apriani, Katarina; Budjang, Gusti; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "the role of parents in child formal education to the family of rice farmers in paling hamlet sub-district of Sanggau Ledoâ€. The subproblems of the research are how the role of parents as facilitators, how the role of parents as a motivator, and how the role of parents as mentors in the formal education of child in the families of rice farmers in the sub-districts of Sanggau Ledo. the method used is qualitative with descriptive type. Data collection tools are guidelines for observation, interviews and documentation. The results of the study show that 1) the role of parents as facilitators is good enough for parents, where parents are directly involved in helping children learn at home and parents provide learning facilities. 2) the role of motivator is also good enough by parents, where parents have provided encouragement and motivation to children to learn, parents also give encouragement to children to take extracurricular in school and give awards and words of praise to children's learning achievements. 3) the role of parents as mentors is good enough for parents, where parents want to help children learn at home even though not fully, because the parents' education is still low. parents also regulate children's learning time by always reminding and telling their children to study at night, they also forbid their children to watch TV before studying. Â Keywords: Role of Parents, Child Formal Education, Family of Rice Farmers